Morphometric Features of the Thoracic Esophagus in Rabbits - Tybinka, А; Zakrevska, M; Kovalskyi, I (Journal of the Hellenic Veterinary Medical Society, 2025)
The morphometric study of the esophagus wall was carried out on the cross-section of the esophagus’ thoracic part in male rabbits (Oryctolagus cuniculus). The area of individual membranes and their structural parts was determined, the correlation between them was established, and the features of their structure and shape were characterized. The superiority of area indicators over linear dimensions (thickness) during morphometric studies were substantiated. The connective tissue’s quantitative and topographic features in general and its fibers in particular were described. It was found that individual differences in the number of mucosal folds caused a high variability in the esophageal lumen area (CV=46.12%), which occupied 8% of the whole organ’s cross-sectional area. These folds also determined the topographic features of the structure and size of the muscularis mucosae and submucosa. Of the total area of the esophageal wall (14.64 mm2), the proportion of individual membranes was as follows: 20.8% - mucous membrane, 11.2% - submucosa, 62.6% - muscle membrane, and 5.4% - serous membrane. More than a half (60.4%) of the mucous membrane area was occupied by the epithelium, the keratinized layer of which was characterized by the highest concentration of neutral mucosubstances and was also the only place for acidic mucosubstances localization. Among three muscular membrane layers, the circular one accounted for the largest area (4.81 mm2), the inner longitudinal layer hit average values (2.85 mm2), and the outer longitudinal layer demonstrated the smallest value (1.49 mm2). Muscle membrane indicators correlated positively with the muscularis mucosae area and the submucosa area. The low and medium variability level of most indicators showed the esophageal wall’s homogenic structure. The serous membrane area was the most variable (CV=58.20%) with the highest density of collagen fibers. The concentration of elastic fibers reached its peak at the junction of the submucosa with the muscle membrane.